Topological Dirac Nodal‐Line Structure in Orthorhombic‐Ti3N2 (Adv. Theory Simul. 3/2018). Issue 3 (7th March 2018) - Yao, Ziwei; Zhang, Xiaoning; Feng, Xing; Wen, Bin
Abstract : As a new type of titanium nitrides phase, o‐Ti3 N2 possesses simultaneous time‐reversal symmetry, spatial inversion symmetry, band inversion and negligible spin‐orbit‐coupling, therefore it is expected to be a topological nodal‐line material. In article number1700018, Bin Wen and co‐workers systematically investigate the electronic and topological properties of o‐Ti3 N2 with a combination of first‐principles calculations and Wannier tight‐binding analysis. The analysis suggests that o‐Ti3 N2 may possess interesting surface transport properties making it a new member in topological materials, with promising novel applications in electronic devices.